Reforming the delivery of public dental services in Ireland: Potential cost implications - Anne Nolan (The Economic and Social Research Institute (ESRI), 2019)
This report, funded by the Department of Health, analyses the costs of alternative packages of publicly financed preventive dental healthcare services for all children and adult medical cardholders. The research estimated the costs of a number of potential care packages with the objective of informing a new national oral health policy. The new policy, Smile agus Sláinte, has been published by the Department of Health. The cost of the services proposed in Smile agus Sláinte draws on costs analysed for a number of different packages examined in the ESRI report.
Keywords: 330